Monitoring beach profile using low altitude aerial imageries - Nurfarahin Zainal, 1993-, author; Mushairry Mustaffar; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2016